Hypervalent Iodine Chemistry - Wirth, Thomas (Topics in Current Chemistry, 2016)
Hypervalent Iodine-Induced Oxidative Couplings (New Metal-Free Coupling Advances and Their Applications in Natural Product Syntheses) -- Toshifumi Dohi and Yasuyuki Kita Phenol Dearomatization with Hypervalent Iodine Reagents -- Stéphane Quideau, Laurent Pouységu, Philippe A. Peixoto, and Denis Deffieux Oxidative Heterocycle Formation Using Hypervalent Iodine(III) Reagents -- Sandip Murarka and Andrey P. Antonchick Aminations with Hypervalent Iodine -- Kilian Muñiz Arylation with Diaryliodonium Salts -- Berit Olofsson Iodanes as Trifluoromethylation Reagents -- Natalja Früh, Julie Charpentier, and Antonio Togni Alkynylation with Hypervalent Iodine Reagents -- Jerome Waser Rearrangements Induced by Hypervalent Iodine -- Gaëtan Maertens, Sylvain Canesi Asymmetric Synthesis with Hypervalent Iodine Reagents -- Ravi Kumar, Thomas Wirth Organoiodine(III) Reagents as Active Participants and Ligands in Transition Metal-Catalyzed Reactions: Iodosylarenes and (Imino)iodoarenes -- John D. Protasiewicz Halogen Bonding in Hypervalent Iodine Compounds -- Luca Catalano, Gabriella Cavallo, Pierangelo Metrangolo , Giuseppe Resnati , Giancarlo Terraneo.